Analisis Literature Review Tentang Tax Avoidance Berdasarkan Artikel Terindeks Scopus - Helmi Budhi Astuti; Fitriana Fitriana; Rachmat Agus Santoso (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study focuses on the influence of Environmental, Social, and Governance (ESG) disclosure and firm size on the performance of companies listed on the Indonesia Stock Exchange (IDX) during the period of 2021-2024. The background of this research is driven by the increasing attention to social responsibility and environmental impacts faced by companies, especially in the energy sector. The main objective of this research is to analyze how ESG disclosures and firm size affect performance, measured using Tobin's Q ratio. The method used is panel data regression analysis with 96 observations from 24 companies, utilizing Eviews 12 software. The data utilized in this study are the annual reports and sustainability reports of each company. The results indicate that social and governance disclosures influence company performance, with coefficient values of -0.331 (negatively influence) and 0.123 (positively influence), respectively. Conversely, environmental disclosure and firm size do not show significant effects, with probability values of 0.5996 and 0.4929. The adjusted R-squared value in this study is 0.780, indicating that firm performance can be explained by the variables examined.The conclusion of this study emphasizes the importance of companies enhancing transparency and accountability through ESG disclosure to improve their performance. The implications of these findings suggest that companies need to be more proactive in fulfilling social and environmental responsibilities to enhance investor trust and market value.